One-pot synthesis of 2-amino-3-cyano-4H-pyrans and pyran-annulated heterocycles using sodium citrate as an organo-salt based catalyst in aqueous ethanol. Issue 1 (2nd January 2022) - Thongni, Aiborlang; Phanrang, Pynskhemborlang T.; Dutta, Arup; Nongkhlaw, Rishanlang
Abstract: Sodium citrate as a highly efficient catalyst is developed for the synthesis of functionalized 2-amino-3-cyano-4 H -pyrans and pyran-annulated heterocycles. This method involves a one-pot three-component reaction of aromatic aldehydes, malononitrile and 1, 3-dicarbonyl compounds with EtOH: H2 O (1:1 v/v) as solvent under room temperature. This protocol presents several advantages such as shorter reaction time, utilization of eco-friendly solvents, operational simplicity, mild reaction conditions, and maximum product yield. Moreover, the use of sodium citrate as an easily available, cheap and benign catalyst plays a pivotal role from a green perspective, considering its high recyclability and easy recovery. Therefore, this present methodology offers numerous possibilities in terms of large-scale industrial syntheses or application to numerous organic conversions. Furthermore, theoretical studies on the mechanistic pathway of the formation of product 4aa were also carried out to determine the catalytic role of sodium citrate on the feasibility of the reaction with DFT method, using B3LYP functional. Graphical Abstract: UF0001